Auf dem Weg zum Räumlichen Leitbild Karlsruhe - Karlsruhe, Stadt [Hrsg.]Neppl, Markus [Red.]Ringler, Harald [Red.]Stippich, Matthias [Red.]Hennig, Christian [Red.]Stoll, Benedikt [Red.] (KIT Scientific Publishing, 2015)
For several years, European cities increasingly focus on long-term planning perspectives due to their spatial development, separated and independent of classic urban land-use planning. As a logical consequence, the city of Karlsruhe define the challenge to develop a spatial mission statement called "Räumliches Leitbild"". For the city anniversary in 2015, most of the development process of the spatial mission statement is documented through an exhibition and the present publication.